Supply Chain Management Performance Analysis of PT. Suzuki Indomobil Motors Using the SCOR Model - Putri, Ersa Cantika; Rahmaniah Malik; Muhammad Fachry Hafid (Journal of Sustainability Industrial Engineering and Management System, 2023)
This research aims to analyze the supply chain performance of PT. Suzuki Indomobil Motor, so that performance improvements can be made in the company's supply chain. This study uses quantitative data sourced from primary data in the form of observational data and interviews, and secondary data in the form of company documents and literature. The steps in the processing carried out were collecting KPI data, pairwise comparison questionnaires, data processing using the SCOR method, and scoring using OMAX and the Traffic Light System. The KPIs with the highest to lowest importance weights in the company are planning (0.343), sourcing (0.247), production (0.177), delivery (0.135), and returns (0.097). Based on OMAX calculations, the supply chain performance that needs to be improved immediately is the percentage of suppliers with EMS (S1.1) and the accuracy of the number of product shipments by suppliers (S1.3). The value of the company's supply chain management obtained is 7.04, where this value indicates that the achievement of the value of the company's supply chain performance is classified as good, but improvements need to be made, especially for indicators that have low performance. As a reference for companies to evaluate and improve supply chain performance, and to monitor supply chain performance periodically. The results of the scoring system show that activities that need to be repaired immediately are activities that are in the red category, namely, Delivery KPI quantity accuracy by supplier and percentage of suppliers with EMS. The high percentage of errors in the delivery of raw materials by suppliers is the cause of delays in the delivery of vehicles to customers by PT. Suzuki Indomobil Motor, so it becomes a consideration for the company whether to continue using the old supplier or to consider other suppliers. Companies should select reliable suppliers so they can provide raw materials of the right quality, right amount, and on time.